Work engagement in public hospitals: a social exchange approach. (2nd January 2018) - Ancarani, Alessandro; Di Mauro, Carmela; Giammanco, Maria Daniela; Giammanco, Giuseppe
Abstract: We develop and test a model that envisages work engagement in public services as determined by interactions with supervisor and co-workers. Specifically, we apply the framework of Social Exchange Theory to explore the impact of Leader–Member exchange (LMX) and Team–Member exchange (TMX) on Work Engagement in the provision of health care in public hospitals. Our investigation suggests that both LMX and TMX represent significant factors associated with work engagement among the hospital medical staff.